A Method for the Numerical Modelling of Embedded Rails and Determining Parameters to be Optimized - Major, Z. (Acta Technica Jaurinensis, 2015)
To carry out FEM modelling two model parameters are needed the elastic (Young) modulus (E) and the Poisson-coefficient (μ). Unfortunately, they are not available in every case, and even if so, they need to be corrected. The author’s earlier examinations have shown that FEM models are extremely sensitive to the value of the Poisson-coefficient. A very small change in them causes a significant difference in determining the elastic coefficient of the rail support. Literature deals with the factors determining the elastic characteristics of embedded rails. In practice the details for the spring constant on a given geometry test specimen (D) and Shore-A hardness (ShA) are available. These details can’t be directly used to create the model but they are suitable to determine parameters that are close to the real values.